Investigation of the reliability of nano-nickel/niobium oxide-based multilayer thin films deposited on polymer substrates for flexible electronic applications - Sahay, Rahul (2024)
Flexible electronics are attractive for a range of applications, such as wearable gadgets and personalized medicine, because of their flexibility, stretchability, and adaptability. However, the reliability of such devices, both mechanical and electrical, is a bottleneck for their widespread application across different use-case scenarios. Here, we report the reliability of nickel-niobium oxide (crystalline-amorphous) sandwich nanolayers on a PI substrate (Ni-Nb2O5-PI) compared to pure nickel (Ni) nanolayers on a PI substrate (Ni-PI) as a potential candidate for electrodes or interconnects for flexible electronic or energy devices. A tailored rate-dependent bending failure/fracture test system was used to analyze the electrical resistance (oscillations) as a function of the loading cycles of the sample deposited on polyimide (PI) (the compliant substrate). Resistance oscillation amplitude during the rate-dependent bending failure/fracture test for Ni-PI (∼6%) was higher compared to that of Ni-Nb2O5-PI (∼2%), suggesting a low resistance change and consequently low mechanical deformation for Ni-Nb2O5-PI. Nanoindentation experiments were also performed to ascertain the hardness and reduced elastic modulus of the samples. Hardness of Ni-PI (∼1.4 GPa) was lower compared to that of Ni-Nb2O5-PI (∼2.4 GPa) suggesting high flow strength for Ni-Nb2O5-PI. Therefore, the incorporation of amorphous niobium oxide into samples otherwise composed of Ni nanolayers significantly improved their fatigue/fracture strength with a slight reduction in electrical conductivity with appreciably low resistance oscillation (amplitude) essential for operational reliability of flexible devices. We also demonstrated that the nickel-niobium oxide/polyimide stack was electrically/mechanically stable up to 500 K stress cycles at a bending radius of 8.5 mm.